Identifiable anti-counterfeit dry-mixed plastering mortar - HE GUOQING; TU YINGQING; LIN HONGYE; ZHANG SHUFANG; XU XIANGWEI; WANG YUNWEI; WANG XIANGLI; XIONG QUANKUI; DAI RENMEI (2014)
The invention discloses identifiable anti-counterfeit dry-mixed plastering mortar. The anti-counterfeit dry-mixed plastering mortar is prepared from the following raw materials by weight ratio: 12-20% of cement, 2.7-5% of secondary fly ash, 73.5-80.5% of river sand, 0.15-0.22% of a water-retaining agent, 0.18-0.36% of a lubricant and 1.47-2.2% of ultraviolet fluorescent anti-counterfeiting particles. The raw materials are stirred and mixed evenly in preparation, and proper water is added to the mixed slurry in use, thereby forming the product. The anti-counterfeit dry-mixed plastering mortar has the technical effects that the ultraviolet fluorescent anti-counterfeiting particles are doped into the premixed dry-mixed plastering mortar, a mortar surface layer emits a dazzling fluorescent light under ultraviolet irradiation, the rate of identification is high, the in-site mixed plastering mortar can be well distinguished from other premixed plastering mortar, the identifiable anti-counterfeit dry-mixed plasterin